Analytical modeling of cross-ply cylindrical composite submersible shell with elastic buckling using first order shear deformation theory - Waqas, Hafiz Muhammad; Shi, Dongyan; Khan, Sohaib Z.; Helal, Mahmoud; Fathallah, Elsayed (Frontiers in Materials, 2022)
This paper presents comprehensive procedures for the mathematical modeling of elastic buckling for submersible composite shells under hydrostatic pressure. First order shear deformation theory (FOSDT) was used for modeling. FOSDT theory was mathematically derived under hydrostatic pressure for composite shells, and it can be used for all types of submersible shells. After the derivation of the theory, mathematical code was formed on MATLAB for this modeling. To check the accuracy range, different types of composite shells, including moderately thick, thick, long, and short, are investigated for the FOSDT formulation. The results were compared with previous studies and finite element analysis FEA. Three types of materials, Carbon/Epoxy, Glass/Epoxy, and Boron/Epoxy, were used with different cross-ply symmetric and unsymmetrical angle con-figurations. The layups used for the analysis were [0/90/0]s, [90/0/90/0]s, [02/902]s, [90/02/90]s, [0/902/0]s, [0/0/0/90]s, [90/90/90/0]s and [0/90].